Bis-Alkenyl Compounds from Group XIV Elements (Si, Ge, Sn): Synthesis, Reactivity, and Applications - Arnaudy, Roxane; Djebbar, Faycel; Tintar, Adrien; Lefèvre, Guillaume (Synthesis, 2025)
This short review summarizes the state-of-the-art for the synthesis of bis-alkenyl compounds from group XIV elements (Si, Ge, Sn). The reported methods that allow formation of such functionalized reagents are discussed, as well as their use as synthetic building blocks in the synthesis of value-added fine chemical targets, polymers, and materials.
Keywords: Bis-Alkenyl; Silicon; Germanium; Tin; Hydroelementation